The Syrian crisis and Attitude League of Arab States Of which 2011_ 2018 - Hassan Mawat Hussein / Husham Naeem Ghlaim lkaapi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The Syrian crisis reflected its effects on its internal conditions and on Arab and regional states and organizations, prompting those countries and organizations to take positions towards the crisis. The League of Arab States was one of the organizations that had a stance towards the crisis, and accordingly, the topic (The Arab League’s position on the Syrian crisis 2011-2018) was chosen. The research plan was defined by two studies. In the first topic it showed the reasons for the outbreak and start of the Syrian crisis, and in the second topic it dealt with the position of the Arab League towards the crisis through the decisions it issued, whether at the level of ministers or Arab summits that were held during the period of the research, and in conclusion the most important results and conclusions are clarified. Reached by the researcher. DOI /10.54633/2333-021-042-021